Surgical management of basicervical fracture neck of femur with dynamic hip screw and de-rotation screw: a prospective study - Kulambi, Vijaykumar S.; Satish, Ajay Shringeri; Rangaraja, Prathik (International Journal of Research in Orthopaedics, 2019)
Background: Basicervical region of femur is that part of femur which is intermediate between neck and intertrochanteric region. Fracture in this region carry substantially higher chances of failure due to greater fracture angle and are rotationally unstable. If treated inadequately they carry very high chances of fracture non-union and theoretically risk of osteonecrosis. The objective of the study was to analyse functional outcome of basicervical fracture neck of femur fixation with dynamic hip screw and de-rotation screw in a tertiary care hospital. Methods: 35 cases of basicervical fracture neck of femur admitted in Chigatteri General Hospital and Bapuji Hospital affiliated to JJM Medical College Davangere, in the period of October 2015 to October 2018. Functional outcome was assessed according to Modified Harris Hip Score after one year of follow up. Results: The fracture union was found in 100% cases, average time period for fracture union was 12.28±3.71 weeks (11-15 weeks range). The results according to Modified Harris hip score were excellent in 70%, good in 11.4%. Fair in 5.7% and poor in 2.8% at the end of one year. The correlation analysis with Pearson’s correlation coefficient (r) was 0.74 which show a highly positive correlation between the union of basicervical fracture neck of femur with dynamic hip screw and derotation screw. Conclusions: With the study of 35 cases of basicervical fracture neck femur we conclude that these are a unique type of fractures mid-way between neck and intertrochanteric fractures with rotational and axial instability, and also risk of osteonecrosis. DHS allows for controlled collapse of the fracture for uneventful healing, and de-rotation screw gives rotational stability.